2014
DOI: 10.5405/jmbe.1695
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This work aims to develop a method for quantitatively analyzing red blood cell (RBC) aggregates under controlled flow conditions. Images of experiments are captured and processed in order to quantify aggregation. The experimental setup consists of RBC suspensions in blood plasma entrained by a phosphate-buffered saline solution in a 110 × 60 µm polydimethylsiloxane microchannel. The experiments are performed by varying the hematocrit (5, 10, and 15%) and the flow rate (Q = 5 and 10 µl/hr) in order to observe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This speckle analysis enables one to measure EA under relatively various hematocrit conditions, compared to other techniques based on image-processing techniques. 10,[27][28][29] Figs. 1(d) and 1(e) show the temporal variations of intensity distribution along with the channel width (y/W Half ), speckle area (A Speckle ) for RBCs suspended in plasma-dextran mixture with a concentration of 0.06% (Ht ¼ 40%), and injection flow rate (Q) of the syringe pump.…”
Section: The Proposed Methods To Measure Ea Based On Speckle Analmentioning
confidence: 99%
See 2 more Smart Citations
“…This speckle analysis enables one to measure EA under relatively various hematocrit conditions, compared to other techniques based on image-processing techniques. 10,[27][28][29] Figs. 1(d) and 1(e) show the temporal variations of intensity distribution along with the channel width (y/W Half ), speckle area (A Speckle ) for RBCs suspended in plasma-dextran mixture with a concentration of 0.06% (Ht ¼ 40%), and injection flow rate (Q) of the syringe pump.…”
Section: The Proposed Methods To Measure Ea Based On Speckle Analmentioning
confidence: 99%
“…To measure the number of RBCs in an aggregate, the area of each rouleaux in binary images was divided by the mean area of a single RBC. Similar to Mehri's method, 29 each aggregate in binary images is labeled for better distinction. The binary images were obtained by thresholding with an optimal value evaluated by using the Otsu's algorithm.…”
Section: E Microscopic Observation For Ea Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…RBC aggregation is a physiological phenomenon; however, it is found significantly elevated in various pathologies because of its sensitivity to inflammation-sensitive proteins (mainly fibrinogen). The distribution of aggregates in microscale blood flows has been recently quantified using image processing techniques; it has been shown that, in general, the size of aggregates in the flow is exponentially distributed (Mehri et al, 2014 andKaliviotis et al, 2017). Furthermore, the distribution of aggregates in bifurcations has been found to be influenced by their spatial distribution in the feeding branch and by the flow conditions in the outlets of the bifurcation (Kaliviotis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present the methodology used to identify, assess and characterize human RBC aggregation subjected to controlled and measurable shear rates in a two-fluid flow microfluidic shearing system (microchannel of 110 × 60 µm 2 ) (Mehri et al 2014(Mehri et al , 2015 using image processing techniques. The methodology was first tested on known diameter hollow glass microspheres and validated by comparing results with the diameters and size distribution obtained provided by the manufacturer.…”
Section: Introductionmentioning
confidence: 99%